Component containing coating and preparation method thereof

By adopting decorative plating coating with multi-layer structure in decorative surface plating products, combined with multi-arc ion plating, HIPIMS and DC magnetron sputtering and other processes, the problems of wear-resistant and fogging in existing products are solved, and a high hardness, wear resistance and aesthetic decorative plating are achieved.

CN119685751APending Publication Date: 2025-03-25NAXAU NEW MATERIALS CORP +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411810645.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing decorative surface plating products are not wear-resistant and scratch-resistant, and the appearance is prone to fog, which cannot meet the decoration needs of 3C products.

Method used

The decorative coating with a multi-layer structure is prepared by processes such as multi-arc ion plating, including a strength support layer, a stress deformation layer and a stress absorbing layer arranged in sequence on the substrate, as well as an external strength support layer and a surface color layer, which are prepared by multi-arc ion plating, HIPIMS and DC magnetron sputtering.

Benefits of technology

It achieves high hardness, wear resistance and scratch resistance, while maintaining the aesthetic appearance and foggy-free characteristics, meeting the decoration needs of 3C products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119685751A_ABST
    Figure CN119685751A_ABST
Patent Text Reader

Abstract

The present application relates to a component comprising a coating and a method of making the same. The coating is arranged on a base body and comprises a plurality of inner layers and an outer layer. Wherein each inner layer comprises a strength support layer A, a stress deformation layer and a stress absorption layer; wherein the outer layer comprises a strength support layer B and a surface color layer. The coating provided by the invention has relatively high hardness and relatively good wear resistance and scratch resistance, and the appearance of the coating meets the requirement of no fogging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of surface treatment technology, and more specifically to a coating and a preparation method thereof. Background Art

[0002] The present application relates to the field of material engineering technology, and specifically to a wear-resistant and scratch-resistant decorative plating coating and its preparation process. With the continuous increase of 3C products, the scale of the 3C decorative coating industry is getting bigger and bigger, but the main problem facing the current decorative plating is that the product is not wear-resistant and scratch-resistant enough, and loses its appearance decorative color. For example, the mobile phone is scratched by the contact and friction of keys, U disks, sand grains, etc. in the pocket, and the smart watch rubs against the desktop during daily work. The Mohs hardness of the products that can be touched in life does not exceed 7 scratches. In addition, even if the product obtained by some surface treatment methods has sufficient hardness, the appearance is foggy and does not meet the decoration requirements of 3C products. Therefore, if a decorative plating coating with a Mohs hardness of 7 scratches and an appearance that meets the decoration requirements can be prepared, it will be a great improvement for the industry. Summary of the invention

[0003] The present invention provides a decorative plating coating to solve at least one problem existing in the related field to at least some extent. The present invention also provides a method for preparing the coating and a product containing the coating.

[0004] In one aspect of the present application, the present application provides a wear-resistant and scratch-resistant component. The component includes a substrate and a coating disposed on the substrate, the coating including a plurality of internal layers and an external layer sequentially disposed in a direction away from the substrate; wherein each internal layer includes the following sublayers: a strength support layer A, the strength support layer A including at least one of the following substances: metal nitride, metal carbide or metal carbonitride; a stress deformation layer, the stress deformation layer including a memory alloy; and a stress absorption layer, the stress absorption layer including a columnar crystal structure with gaps. The external layer includes the following sublayers sequentially disposed in a direction away from the substrate: a strength support layer B, the strength support layer B including at least one of the following substances: metal nitride, metal carbide or metal carbonitride; and a surface color layer.

[0005] In some embodiments, there are 5 to 15 internal layers, wherein the first internal layer contacting the substrate includes a strength support layer A, a stress deformation layer, and a stress absorption layer sequentially arranged in a direction away from the substrate.

[0006] In some embodiments, except for the first internal layer contacting the substrate, the remaining multiple internal layers include a strength support layer A, a stress deformation layer, and a stress absorption layer sequentially arranged in a direction away from the substrate, or include a strength support layer A, a stress absorption layer, and a stress deformation layer sequentially arranged in a direction away from the substrate. That is, except for the first internal layer, the positions of the stress deformation layer and the stress absorption layer in the remaining internal layers can be interchanged.

[0007] In some embodiments, the metal in the metal nitride, the metal carbide or the metal carbonitride in the strength support layer A and the strength support layer B is independently selected from at least one of Cr, Al, Ti, Ta, Zr, Fe, Cu, Ni or V.

[0008] In some embodiments, the memory alloy in the stress-strain layer includes at least one of NiTi, NiTiCu, CuZn, CuZnAl, CuAlNi, NiMnGa, NiMnIn, or CoNi.

[0009] In some embodiments, the stress absorbing layer includes at least one of TiN and CrN.

[0010] In some embodiments, the material of the corresponding surface color layer is selected according to different color requirements, for example, Cr is selected to obtain CrN steel color, and Ti is selected to obtain TiN gold color.

[0011] In some embodiments, each of the inner layers or the outer layer satisfies at least one of the following (1)-(11):

[0012] (1) The hardness of the strength support layer A and the strength support layer B are independently HV2000 to HV3600;

[0013] (2) The hardness of the stress deformation layer is HV300 to HV900;

[0014] (3) The hardness of the stress absorbing layer is HV1500 to HV2000;

[0015] (4) The hardness of the surface color layer is HV1500 to HV2600;

[0016] (5) The size of the columnar crystals in the stress absorption layer is at least 100-300 nanometers;

[0017] (6) The thickness of the strength support layer A and the strength support layer B are independently 0.3-1.5 μm;

[0018] (7) The thickness of the stress deformation layer is 0.5-1.5 microns;

[0019] (8) The thickness of the stress absorption layer is 0.2-1 micrometer;

[0020] (9) The thickness of the surface color layer is 0.3-1 micron;

[0021] (10) The total thickness of the coating is 8-20 μm; or

[0022] (11) The total hardness of the coating is HV1500-HV3000.

[0023] In another aspect of the present application, the present application provides a method for preparing the above-mentioned component. The method comprises the following steps:

[0024] (1) forming a strength support layer A on the surface of the substrate of the component;

[0025] (2) forming a stress deformation layer on the strength support layer A;

[0026] (3) forming a stress absorbing layer on the stress deformation layer;

[0027] (4) repeating steps (1) to (3) for 4 to 15 cycles, wherein in each cycle, the order of the steps is independently steps (1), (2) and (3) or steps (1), (3) and (2);

[0028] (5) forming a strength support layer B on the stress deformation layer or stress absorption layer obtained after the cycle of step (4); and

[0029] (6) A surface color layer is formed on the strength support layer B.

[0030] In some embodiments, steps (1) and (5) adopt a multi-arc ion plating process, which includes introducing N gas, maintaining the gas pressure at 1-6 Pa, setting the target current at 60-200 A, the bias voltage at 60-200 V, turning on the metal nitride, metal carbide or metal carbonitride target, and the coating time is 10-20 min.

[0031] In some embodiments, the step (2) adopts a high-energy pulse magnetron sputtering process, which includes introducing Ar gas, maintaining the gas pressure at 0.1-0.8 Pa, bias voltage 0-60 V, setting process parameters: power 8-10 KW, frequency 200-800 khz, pulse width 100-500 us, turning on the memory alloy target, and the coating time is 1-2 hours.

[0032] In some embodiments, the step (3) adopts a DC magnetron sputtering process, which includes introducing Ar and N gases, maintaining the gas pressure at about 0.5 Pa, turning on the Cr target, setting the target current to 20 A, setting the bias voltage to 30 V, and the coating time to 5-15 min.

[0033] In some embodiments, the step (6) adopts a high-energy pulsed magnetron sputtering process, which includes introducing Ar and at least one of the following gases: N, C 2 H 2 and O 2 , turn on the color target and set the process parameters: power 8-10KW, frequency 200-800khz, pulse width 100-500us, time 30-120min.

[0034] In some embodiments, the material of the substrate includes a steel substrate or an aluminum substrate.

[0035] In some embodiments, the method further includes a plasma cleaning process before step (1), and preferably the plasma cleaning process includes: after the vacuum degree in the furnace reaches 5*10-3Pa and the temperature reaches 300 degrees, Ar gas is introduced, the gas pressure is maintained at 0.3Pa-0.9Pa, the ion source is turned on, the ion source voltage is set at 400-800V, the ion source duty cycle is 20-80%, the bias voltage is set at 100-200V, and plasma cleaning is performed for 5-60min.

[0036] In another aspect of the present application, the present application provides a shell structure, which includes the component described in the embodiment of the present application or includes the component prepared by the method described in the embodiment of the present application.

[0037] In yet another aspect of the present application, the present application provides an electronic device, which includes an electronic device and a housing structure of the present application, wherein the housing structure is located outside the electronic device.

[0038] The embodiment of the present application provides a decorative plating coating and a preparation method thereof, wherein the decorative plating coating includes a plurality of cycles of strength support layers, stress deformation layers, stress absorption layers, and a surface color layer of the decorative coating. The strength support layer ensures that the hardness of the coating does not scratch the substrate; the stress deformation layer adopts memory metal, which has large elastic stress deformation, resists external force deformation and recovers after deformation, reducing the impact on the substrate; the stress absorption layer can transmit external stress due to the presence of columnar crystal gaps to reduce the impact on the substrate. The decorative plating coating has high hardness, good wear resistance and scratch resistance, and the appearance meets the requirements of decoration without fogging.

[0039] Additional aspects and advantages of the embodiments of the present application will be described and shown in part in the subsequent description, or explained through the implementation of the embodiments of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 : Schematic diagram of the structure of the coating of Example 1.

[0041] Figure 2 : Appearance pictures of the coatings of Example 1, Comparative Examples 3 and 4. DETAILED DESCRIPTION

[0042] The embodiments of the present application will be described in detail below. The embodiments of the present application should not be interpreted as limiting the present application.

[0043] In the detailed description and claims, a list of items connected by the terms "one of," "one of," "a kind of," or other similar terms may mean any of the listed items. For example, if items A and B are listed, the phrase "one of A and B" means only A or only B. In another example, if items A, B, and C are listed, the phrase "one of A, B, and C" means only A; only B; or only C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0044] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0045] The following descriptions of the embodiments are made with reference to the attached drawings to illustrate specific embodiments of the present invention that can be implemented. Furthermore, the directional terms mentioned in the present invention, such as up, down, top, bottom, front, back, left, right, inside, outside, side, periphery, center, horizontal, lateral, vertical, longitudinal, axial, radial, topmost or bottommost, etc., are only with reference to the directions of the attached drawings. Therefore, the directional terms used are used to illustrate and understand the present invention, but are not used to limit the present invention.

[0046] With respect to the numerical values ​​presented herein, the measured values ​​should be understood to have an acceptable degree of error due to the nature or precision of the measurements. Typical exemplary degrees of error may be within ±10% or ±5% of a given value or range of values.

[0047] 1. Decorative coating

[0048] In one aspect of the present application, the present application provides a wear-resistant and scratch-resistant component. The component includes a substrate and a coating disposed on the substrate, the coating including a plurality of internal layers and an external layer sequentially disposed in a direction away from the substrate; wherein each internal layer includes the following sublayers: a strength support layer A, the strength support layer A including at least one of the following substances: metal nitride, metal carbide or metal carbonitride; a stress deformation layer, the stress deformation layer including a memory alloy; and a stress absorption layer, the stress absorption layer including a columnar crystal structure with gaps. The external layer includes the following sublayers sequentially disposed in a direction away from the substrate: a strength support layer B, the strength support layer B including at least one of the following substances: metal nitride, metal carbide or metal carbonitride; and a surface color layer.

[0049] In some embodiments, the number of the internal layers is 5-15. The first internal layer in contact with the substrate includes a strength support layer A, a stress deformation layer, and a stress absorption layer sequentially arranged in a direction away from the substrate. In some embodiments, the number of the internal layers is 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, or a range consisting of any two of the above values. For example, the number of internal layers in Example 1 of the present application is 6, in Example 2 is 9, in Example 3 is 5, and in Example 4 is 7.

[0050] In some embodiments, except for the first internal layer contacting the substrate, the remaining multiple internal layers include a strength support layer A, a stress deformation layer, and a stress absorption layer sequentially arranged in a direction away from the substrate, or include a strength support layer A, a stress absorption layer, and a stress deformation layer sequentially arranged in a direction away from the substrate. That is, except for the first internal layer, the positions of the stress deformation layer and the stress absorption layer in the remaining internal layers can be interchanged.

[0051] In some embodiments, the metal in the metal nitride, the metal carbide or the metal carbonitride in the strength support layer A and the strength support layer B is independently selected from at least one of Cr, Al, Ti, Ta, Zr, Fe, Cu, Ni or V. For example, the metal may be a combination of Cr and Al or a combination of Al and Ti.

[0052] In some embodiments, the memory alloy in the stress-strain layer includes at least one of NiTi, NiTiCu, CuZn, CuZnAl, CuAlNi, NiMnGa, NiMnIn, or CoNi.

[0053] In some embodiments, the stress absorbing layer includes at least one of TiN and CrN.

[0054] In some embodiments, the material of the corresponding surface color layer is selected according to different color requirements, for example, Cr is selected to obtain CrN steel color, and Ti is selected to obtain TiN gold color.

[0055] In some embodiments, each of the inner layers or the outer layer satisfies at least one of the following (1)-(11):

[0056] (1) The hardness of the strength support layer A and the strength support layer B are independently HV2000 to HV3600;

[0057] (2) The hardness of the stress deformation layer is HV300 to HV900;

[0058] (3) The hardness of the stress absorbing layer is HV1500 to HV2000;

[0059] (4) The hardness of the surface color layer is HV1500 to HV2600;

[0060] (5) The size of the columnar crystals in the stress absorption layer is at least 100-300 nanometers;

[0061] (6) The thickness of the strength support layer A and the strength support layer B are independently 0.3-1.5 μm;

[0062] (7) The thickness of the stress deformation layer is 0.5-1.5 microns;

[0063] (8) The thickness of the stress absorption layer is 0.2-1 micrometer;

[0064] (9) The thickness of the surface color layer is 0.3-1 micron;

[0065] (10) The total thickness of the coating is 8-20 μm; or

[0066] (11) The total hardness of the coating is HV1500-HV3000.

[0067] In some embodiments, the hardness of the strength support layer A and the strength support layer B are independently HV2000, HV2200, HV2400, HV2600, HV2800, HV3000, HV3400, HV3600 or a range consisting of any two of the above values.

[0068] In some embodiments, the hardness of the stress-deformation layer is HV300, HV450, HV600, HV750, HV900, or a range consisting of any two of the above values.

[0069] In some embodiments, the hardness of the stress absorbing layer is HV1500, HV1750, HV2000, or a range consisting of any two of the above values.

[0070] In some embodiments, the hardness of the surface color layer is HV1500, HV1700, HV2000, HV2200, HV2400, HV2600, or a range consisting of any two of the above values.

[0071] In some embodiments, the size of the columnar crystals in the stress absorption layer is 100 nanometers, 200 nanometers, or 300 nanometers.

[0072] In some embodiments, the thickness of the strength support layer A and the strength support layer B are independently 0.3 μm, 0.4 μm, 0.5 μm, 0.8 μm, 1 μm, 1.2 μm, 1.5 μm or a range consisting of any two of the above values.

[0073] In some embodiments, the thickness of the stress-strain layer is 0.5 μm, 0.6 μm, 0.8 μm, 1 μm, 1.2 μm, 1.5 μm, or a range consisting of any two of the above values.

[0074] In some embodiments, the thickness of the stress absorption layer is 0.2 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.8 μm, 1 μm, or a range consisting of any two of the above values.

[0075] In some embodiments, the thickness of the surface color layer is 0.3 μm, 0.5 μm, 0.7 μm, 1 μm, or a range consisting of any two of the above values.

[0076] In some embodiments, the total thickness of the coating is 8 μm, 10 μm, 12 μm, 15 μm, 17 μm, 20 μm, 22 μm, or a range consisting of any two of the above values, for example, 10-15 μm.

[0077] In some embodiments, the total hardness of the coating is HV1500, HV2000, HV2600, HV3000, or a range consisting of any two of the above values, for example, it can be HV2000-HV2600.

[0078] In another aspect of the present application, the present application provides a method for preparing the above-mentioned component. The method comprises the following steps:

[0079] (1) forming a strength support layer A on the surface of the substrate of the component;

[0080] (2) forming a stress deformation layer on the strength support layer A;

[0081] (3) forming a stress absorbing layer on the stress deformation layer;

[0082] (4) repeating steps (1) to (3) for 4 to 15 cycles, wherein in each cycle, the order of the steps is independently steps (1), (2) and (3) or steps (1), (3) and (2);

[0083] (5) forming a strength support layer B on the stress deformation layer or stress absorption layer obtained after the cycle of step (4); and

[0084] (6) A surface color layer is formed on the strength support layer B.

[0085] In some embodiments, the number of times steps (1)-(3) are repeated in step (4) is 5, 6, 7, 8, 9, 10, 11, 12, 13, 15, 15 times or a range consisting of any two of the above values.

[0086] In some embodiments, steps (1) and (5) adopt a multi-arc ion plating process, which includes introducing N gas, maintaining the gas pressure at 1-6Pa (e.g., 3Pa, 3.5Pa, 5Pa), setting the target current at 60-200A (e.g., 60A, 120A, 150A), biasing at 60-200V (e.g., 90V, 150V), turning on the target material of metal nitride, metal carbide or metal carbonitride (e.g., Cr80Al20, Al50Ti50, Al70Ti30, Cr50Al50), and the coating time is 10-120min (e.g., 30min, 35min, 40min, 75min, 120min).

[0087] In some embodiments, the step (2) adopts a high-energy pulse magnetron sputtering process, which includes introducing Ar gas, maintaining the gas pressure at 0.1-0.8Pa (for example, 0.2Pa, 0.3Pa, 0.5Pa), biasing 0-60V (for example, 30V, 60V), setting process parameters: power 8-10KW (for example, 8KW), frequency 200-800khz (for example, 450khz), pulse width 100-500us (for example, 150us, 300us), turning on the memory alloy target (for example, Ni50Ti50, Ni45Ti50Cu5), and the coating time is 1-2h (for example, 1h).

[0088] In some embodiments, the step (3) adopts a DC magnetron sputtering process, which includes introducing Ar and N gases (with a partial pressure ratio of 2:3 or 3:2), maintaining the gas pressure at about 0.5 Pa, turning on the Cr target, setting the target current to 20 A, setting the bias voltage to 30 V, and the coating time to 5-15 min (e.g., 10 min, 15 min).

[0089] In some embodiments, the step (6) adopts a high-energy pulsed magnetron sputtering process, which includes introducing Ar and at least one of the following gases: N, C 2 H 2 and O 2 , turn on the color target, set the process parameters: power 8-10KW, frequency 200-800khz (e.g. 450), pulse width 100-500us (e.g. 150), time 30-120min (e.g. 60min, 80min, 120min). In some embodiments, the ratio of Ar to N is 2:1-5:1. In some embodiments, Ar, N and C 2 H 2 The ratio is 5:3:3 or 150:50:1.

[0090] In some embodiments, the material of the substrate includes a steel substrate (eg, 316L stainless steel) or an aluminum substrate.

[0091] In some embodiments, the method further includes a plasma cleaning process before step (1), and preferably the plasma cleaning process includes: after the vacuum degree in the furnace reaches 5*10-3Pa and the temperature reaches 300 degrees, Ar gas is introduced, the gas pressure is maintained at 0.3Pa-0.9Pa (for example, 0.5Pa), the ion source is turned on, the ion source voltage is set to 400-800V (for example, 400V, 500V), the ion source duty cycle is 20-80% (for example, 45%, 50%), the bias voltage is set to 100-200V (for example, 120V, 150V), and plasma cleaning is performed for 5-60min (for example, 15min, 20min).

[0092] 2. 3C Products

[0093] The 3C products of the present application include any products that can use decorative plating coatings, and specific examples thereof include all kinds of electronic devices, such as computers, tablet computers, mobile phones or digital audio players, etc.

[0094] Example

[0095] Hereinafter, the present application will be described in more detail with reference to Examples and Comparative Examples, but the present application is not limited to these Examples unless departing from the gist of the present application.

[0096] The coating processes used in this article are multi-arc ion plating process, high energy pulsed magnetron sputtering (HIPIMS) process and DC magnetron sputtering process, but those skilled in the art understand that coating also includes other different forms of thin film deposition technology, as long as the process can achieve the technical effect of this application, it is within the scope of this application.

[0097] Unless otherwise stated, the materials used in this application are all commercially available.

[0098] Example 1

[0099] The structural schematic diagram of the decorative plating coating of this embodiment is as follows Figure 1 As shown, 7 repeated internal layers and 1 external layer are sequentially arranged on the substrate 6. Each internal layer sequentially includes a strength support layer 1, a stress deformation layer 2, and a stress absorption layer 3. The external layer sequentially includes a strength support layer 4 and a surface color layer 5. The specific process is as follows:

[0100] 1. Plasma cleaning process: After cleaning, push the 316L stainless steel substrate product into the furnace, turn on the mechanical pump, Roots pump, and molecular pump to evacuate, and set the heating tube temperature to 300 degrees. After the vacuum degree in the furnace reaches 5*10-3Pa and the temperature reaches 300 degrees, introduce Ar gas, maintain the gas pressure at 0.5Pa, turn on the ion source, set the ion source voltage at 400V, the ion source duty cycle at 50%, set the bias voltage at 120V, and perform the plasma cleaning process. The cleaning time is 20 minutes.

[0101] 2. Strength support layer 1: The first strength support layer is deposited on the surface of the product by using multi-arc ion plating technology, N gas is introduced, the gas pressure is maintained at 3.5 pa, the target current is set at 150 A, the bias voltage is set at 150 V, the Cr50Al50 target material is turned on, and the coating time is 30 min. The surface hardness of the strength support layer 1 of this embodiment reaches HV2400, and the thickness is about 0.4 μm.

[0102] 3. Stress deformation layer 2: Turn on HIPIMS to deposit the second stress deformation layer on the basis of the first layer, introduce Ar, maintain the gas pressure at 0.3Pa, set the bias voltage to 30V, set the HIPIMS parameters: power 8KW, frequency 450khz, pulse width 150us, turn on Ni50Ti50, and the coating time is 1h. The surface hardness of the stress deformation layer 2 of this embodiment reaches HV450 and the thickness is about 0.5μm.

[0103] 4. Stress absorbing layer 3: Turn on DC, introduce Ar and N gas (argon partial pressure is 0.3Pa, nitrogen partial pressure is 0.2PA), keep the gas pressure at about 0.5Pa, turn on the Cr target, set the target current to 20A, set the bias voltage to 30V, and the coating time to 10min. The surface hardness of the stress absorbing layer 3 of this embodiment reaches HV1500, and the thickness is about 0.6μm.

[0104] 5. Turn on the device cycle mode and repeat steps 2-4 for 5 cycles.

[0105] 6. Strength support layer 4: Multi-arc ion plating technology was used again, N gas was introduced, the gas pressure was maintained at 3.5 pa, the target current was set at 150 A, the bias voltage was set at 150 V, the Cr50Al50 target material was turned on, and the coating time was 35 min. The surface hardness of the strength support layer 4 of this embodiment reached HV2400, and the thickness was about 0.5 μm.

[0106] 7. Surface color layer 5: Turn on HIPIMS, introduce Ar and N gas (argon partial pressure is 0.2Pa and nitrogen partial pressure is 0.1Pa), keep the pressure at 0.3Pa, set the HIPIMS power to 10KW, frequency to 450Khz, pulse width to 150us, turn on the Cr target to deposit steel color, and the deposition time is 60min. The surface hardness of the surface color layer 5 of this embodiment reaches HV2000, and the thickness is about 0.5μm.

[0107] 8. After coating is completed, the product is cooled and taken out of the oven.

[0108] Example 2

[0109] 1. Plasma cleaning process: After cleaning, push the 316L stainless steel substrate product into the furnace, turn on the mechanical pump, Roots pump, and molecular pump to evacuate, and set the heating tube temperature to 300 degrees. After the vacuum degree in the furnace reaches 5*10-3Pa and the temperature reaches 300 degrees, introduce Ar gas, maintain the gas pressure at 0.5Pa, turn on the ion source, set the ion source voltage at 500V, the ion source duty cycle at 45%, set the bias voltage at 150V, and carry out the plasma cleaning process. The cleaning time is 15 minutes.

[0110] 2. Strength support layer 1: The first strength support layer is deposited on the surface of the product by using multi-arc ion plating technology, N gas is introduced, the gas pressure is maintained at 3.0 pa, the target current is set at 120 A, the bias voltage is set at 90 V, the Al70Ti30 target material is turned on, and the coating time is 35 min. The surface hardness of the strength support layer 1 of this embodiment reaches HV2800, and the thickness is about 0.3 μm.

[0111] 3. Stress deformation layer 2: Turn on HIPIMS to deposit the second stress deformation layer on the basis of the first layer, introduce Ar, maintain the gas pressure at 0.2Pa, set the bias voltage to 60V, set the HIPIMS parameters: power 8KW, frequency 450khz, pulse width 150us, turn on Ni45Ti50Cu5, and the coating time is 1h. The surface hardness of the stress deformation layer 2 of this embodiment reaches HV300, and the thickness is about 0.6μm.

[0112] 4. Stress absorbing layer 3: Turn on DC, introduce Ar and N gas (argon partial pressure is 0.2Pa and nitrogen partial pressure is 0.3Pa), keep the gas pressure at about 0.5Pa, turn on the Cr target, set the target current to 20A, set the bias voltage to 30V, and the coating time to 10min. The surface hardness of the stress absorbing layer 3 of this embodiment reaches HV1500, and the thickness is about 0.6μm.

[0113] 5. Turn on the device cycle mode and repeat steps 2-4 for 8 cycles.

[0114] 6. Strength support layer 4: Start multi-arc ion plating again, introduce N gas, keep the gas pressure at 3.0pa, set the target current at 120A, set the bias voltage at 90V, start Al70Ti30 target material, and the coating time is 75min. The surface hardness of the strength support layer 4 of this embodiment reaches HV2400 and the thickness is about 1μm.

[0115] 7. Surface color layer 5: Turn on HIPIMS and introduce Ar, N, C 2 H 2 (gas flow ratio is 150:50:1), keep the gas pressure at 0.4Pa, set the hipims power to 8KW, frequency to 200Khz, pulse width to 500us, turn on the Ti target, and the deposition time to 120min. The surface hardness of the surface color layer 5 of this embodiment reaches HV2600, and the thickness is about 0.5μm.

[0116] 8. After coating is completed, the product is cooled and taken out of the oven.

[0117] Example 3

[0118] 1. Plasma cleaning process: After cleaning, push the 316L stainless steel substrate product into the furnace, turn on the mechanical pump, Roots pump, and molecular pump to evacuate, and set the temperature of the heating tube to 300 degrees. After the vacuum degree in the furnace reaches 5*10-3Pa and the temperature reaches 300 degrees, introduce Ar gas, maintain the gas pressure at 0.5Pa, turn on the ion source, set the ion source voltage at 500V, the ion source duty cycle at 45%, set the bias voltage at 150V, and carry out the plasma cleaning process. The cleaning time is 15 minutes.

[0119] 2. Strength support layer 1: The first strength support layer is deposited on the surface of the product by using multi-arc ion plating technology, N gas is introduced, the gas pressure is maintained at 3.0 pa, the target current is set at 120 A, the bias voltage is set at 90 V, the Al50Ti50 target material is turned on, and the coating time is 40 min. The surface hardness of the strength support layer 1 of this embodiment reaches HV2000, and the thickness is about 0.3 μm.

[0120] 3. Stress deformation layer 2: Turn on HIPIMS to deposit the second stress deformation layer on the basis of the first layer, introduce Ar, maintain the gas pressure at 0.2Pa, set the bias voltage to 60V, set the HIPIMS parameters: power 8KW, frequency 450khz, pulse width 150us, turn on Ni45Ti50Cu5, and the coating time is 1h. The surface hardness of the stress deformation layer 2 of this embodiment reaches HV300, and the thickness is about 0.5μm.

[0121] 4. Stress absorbing layer 3: Turn on DC, introduce Ar and N gas (argon partial pressure is 0.2Pa, nitrogen partial pressure is 0.3Pa), keep the gas pressure at about 0.5Pa, turn on the Cr target, set the target current to 20A, set the bias voltage to 30V, and the coating time to 10min. The surface hardness of the stress absorbing layer 3 of this embodiment reaches HV1500, and the thickness is about 0.5μm.

[0122] 5. Turn on the device cycle mode and repeat steps 2-4 for 4 cycles.

[0123] 6. Strength support layer 4: Start multi-arc ion plating again, introduce N gas, keep the gas pressure at 3.0pa, set the target current at 120A, set the bias voltage at 90V, start Al50Ti50 target material, and the coating time is 120min. The surface hardness of the strength support layer 4 of this embodiment reaches HV2000, and the thickness is about 1μm.

[0124] 7. Surface color layer 5: Turn on HIPIMS, introduce Ar, N, C2H2 (gas flow ratio is 5:3:3), keep the gas pressure at 0.4 Pa, set the HIPIMS power to 8KW, frequency to 200Khz, pulse width to 500us, turn on the Ti target, and the deposition time is 120min. The surface hardness of the surface color layer 5 of this embodiment reaches HV1500, and the thickness is about 0.5μm.

[0125] 8. After coating is completed, the product is cooled and taken out of the oven.

[0126] Example 4

[0127] The structural schematic diagram of the decorative plating coating of this embodiment is as follows Figure 1 As shown, 7 repeated internal layers and 1 external layer are sequentially arranged on the substrate 6. Each internal layer sequentially includes a strength support layer 1, a stress deformation layer 2, and a stress absorption layer 3. The external layer sequentially includes a strength support layer 4 and a surface color layer 5. The specific process is as follows:

[0128] 1. Plasma cleaning process: After cleaning, push the 316L stainless steel substrate product into the furnace, turn on the mechanical pump, Roots pump, and molecular pump to evacuate, and set the heating tube temperature to 300 degrees. After the vacuum degree in the furnace reaches 5*10-3Pa and the temperature reaches 300 degrees, introduce Ar gas, maintain the gas pressure at 0.5Pa, turn on the ion source, set the ion source voltage at 400V, the ion source duty cycle at 50%, set the bias voltage at 120V, and carry out the plasma cleaning process. The cleaning time is 20 minutes.

[0129] 2. Strength support layer 1: The first strength support layer is deposited on the surface of the product by using multi-arc ion plating technology, N gas is introduced, the gas pressure is maintained at 3.5 pa, the target current is set at 150 A, the bias voltage is set at 150 V, the Cr80Al20 target material is turned on, and the coating time is 40 min. The surface hardness of the strength support layer 1 of this embodiment reaches HV3400, and the thickness is about 0.8 μm.

[0130] 3. Stress deformation layer 2: Turn on HIPIMS to deposit the second stress deformation layer on the basis of the first layer, introduce Ar, maintain the gas pressure at 0.3Pa, set the bias voltage to 30V, set the HIPIMS parameters: power 8KW, frequency 450khz, pulse width 150us, turn on Ni50Ti50, and the coating time is 1h. The surface hardness of the stress deformation layer 2 of this embodiment reaches HV450 and the thickness is about 1μm.

[0131] 4. Stress absorbing layer 3: Turn on DC, introduce Ar and N gas (argon partial pressure is 0.3Pa, nitrogen partial pressure is 0.2PA), keep the gas pressure at about 0.5Pa, turn on the Cr target, set the target current to 20A, set the bias voltage to 30V, and the coating time to 10min. The surface hardness of the stress absorbing layer 3 of this embodiment reaches HV1500, and the thickness is about 1μm.

[0132] 5. Turn on the device cycle mode and repeat steps 2-4 for 6 cycles.

[0133] 6. Strength support layer 4: Multi-arc ion plating technology was used again, N gas was introduced, the gas pressure was maintained at 3.5 pa, the target current was set at 150 A, the bias voltage was set at 150 V, the Cr80Al20 target material was turned on, and the coating time was 35 min. The surface hardness of the strength support layer 4 of this embodiment reached HV3400, and the thickness was about 1 μm.

[0134] 7. Surface color layer 5: Turn on HIPIMS, introduce Ar and N gas (argon partial pressure is 0.25Pa and nitrogen partial pressure is 0.05Pa), keep the pressure at 0.3Pa, set the HIPIMS power to 10KW, frequency to 450Khz, pulse width to 150us, turn on the Cr target to deposit steel color, and the deposition time is 80min. The surface hardness of the surface color layer 5 of this embodiment reaches HV2400, and the thickness is about 1μm.

[0135] 8. After coating is completed, the product is cooled and taken out of the oven.

[0136] Comparative Example 1

[0137] 316L stainless steel sheet, no coating.

[0138] Comparative Example 2

[0139] 316L stainless steel sheet, using the following traditional decorative technology steel color process:

[0140] 1. Pumping: Turn on the mechanical pump, Roots pump, and molecular pump in sequence to pump the gas pressure in the furnace to 8*10-3Pa.

[0141] 2. Metal etching: introduce Ar gas to make the gas pressure at 3PA and set the bias voltage to 1000V, start the multi-arc ion plating Cr target, and etch for 30S.

[0142] 3. Coating: introduce Ar and N gas (argon partial pressure is 0.2Pa and nitrogen partial pressure is 0.3Pa), turn on the medium frequency magnetron sputtering Cr target, set the bias voltage to 90V, and the deposition time to 2h.

[0143] Comparative Example 3

[0144] 316L stainless steel sheet, using the following traditional decorative plating technology to prepare steel color and increase its film thickness:

[0145] 1. Pumping: Turn on the mechanical pump, Roots pump, and molecular pump in sequence to pump the gas pressure in the furnace to 8*10-3Pa.

[0146] 2. Metal etching: introduce Ar gas to make the gas pressure at 3PA and set the bias voltage to 1000V, start the multi-arc ion plating Cr target, and etch for 30S.

[0147] 3. Coating: introduce Ar and N gas (argon partial pressure is 0.2Pa and nitrogen partial pressure is 0.3Pa), turn on the medium frequency magnetron sputtering Cr target, set the bias voltage to 90V, and the deposition time is 20h.

[0148] Comparative Example 4

[0149] 316L stainless steel sheet, using the following multi-arc ion plating technology, preparation of CrAlN process:

[0150] 1. Pumping: Turn on the mechanical pump, Roots pump, and molecular pump in sequence to pump the gas pressure in the furnace to 5*10-3Pa.

[0151] 2. AEGD etching: Ar gas was introduced to make the gas pressure at 3PA and the bias voltage was set to 200V. The multi-arc rectangular ion plating Cr target was turned on and the baffle was set in front of the Cr target for etching time of 20min.

[0152] 3. Coating: introduce Ar and N gas (argon partial pressure is 0.2Pa and nitrogen partial pressure is 0.3Pa), turn on the multi-arc Cr target, set the bias voltage to 60V, and the deposition time is 1.5h.

[0153] Performance Testing

[0154] Hardness: Refer to standard ISO14577 and use nano indenter to test the hardness of surface coating.

[0155] Mohs hardness scratch: Installed on a dedicated Mohs hardness tester, the load is 500gf, the tip of the Mohs hardness pen contacts the surface to be tested, and the angle between the pen tip and the surface to be tested is 45°. Push the pen forward at a speed of 0.5mm / s to 1mm / s for about 5mm (when the sample length is less than 5mm, try to test on the sample surface), and replace Mohs hardness pens with different hardness values ​​until obvious scratches appear.

[0156] Steel wool scratch: Use a dedicated steel wool testing instrument, with dedicated steel wool (steel wool model: #0000, manufacturer: Bon Star STEEL WOOL), apply a load of 500gf, the test head area is 2*2cm, rub back and forth on the sample surface at a speed of 40cycle / min and a stroke of about 30mm.

[0157] Table 1. Test results of various embodiments and comparative examples

[0158] OK means the appearance is neither foggy nor hazy.

[0159] The basic performance test of the prepared coating was carried out, and the results are shown in Table 1. From Comparative Examples 1-4, it can be seen that as the thickness increases, the appearance becomes hazy; while from Examples 1 and 2, it can be seen that the coating of the present application can maintain a good appearance even though the thickness reaches 15 μm. The appearance photos of Example 1 and Comparative Examples 3 and 4 are shown in Figure 2 .

[0160] In addition, it can be seen from Comparative Examples 1-4 that as the hardness increases, the number of steel wool scratches increases, but in Comparative Example 4 with a hardness of 3000 HV, the Mohs hardness scratch can only reach 5. From Examples 1 and 2, it can be seen that although the hardness of the coating of the present application only rises to 2000 HV, it can achieve a Mohs hardness of 7 scratches and 4000 steel wool scratches.

[0161] In addition, it can be seen from Examples 1-4 that the coating thickness and hardness have an impact on product performance (appearance and scratches), wherein in order to obtain better performance, the coating thickness is preferably 10-15 μm and the hardness is preferably 2000 HV-2600 HV.

[0162] It should be noted that the coating or shell structure provided by the present application can be applied not only to electronic devices, but also to the decoration field, such as automobile shell decoration, home decoration, etc.

[0163] References throughout the specification to "some embodiments", "partial embodiments", "one embodiment", "another example", "example", "specific example" or "partial example" mean that at least one embodiment or example in the present application includes the specific features, structures, materials or characteristics described in the embodiment or example. Therefore, descriptions appearing in various places throughout the specification, such as: "in some embodiments", "in an embodiment", "in one embodiment", "in another example", "in an example", "in a specific example" or "example", do not necessarily refer to the same embodiment or example in the present application. In addition, the specific features, structures, materials or characteristics herein may be combined in one or more embodiments or examples in any suitable manner.

[0164] Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limitations on the present application, and that changes, substitutions and modifications may be made to the embodiments without departing from the spirit, principles and scope of the present application.

Claims

1. A wear-resistant and scratch-resistant component, comprising a substrate and a coating disposed on the substrate, wherein the coating comprises a plurality of inner layers and an outer layer disposed sequentially in a direction away from the substrate; Each inner layer consists of the following sublayers: Strength support layer A, the strength support layer A comprises at least one of the following substances: metal nitride metal carbides or metal carbonitrides; a stress-strain layer, the stress-strain layer comprising a memory alloy; and a stress absorbing layer, the stress absorbing layer comprising a columnar crystal structure having gaps; and The outer layer comprises the following sublayers arranged in sequence in a direction away from the substrate: Strength support layer B, the strength support layer B comprises at least one of the following substances: metal nitride metal carbides or metal carbonitrides; and Surface color layer.

2. The component according to claim 1, wherein the number of the internal layers is 5-15, wherein the first internal layer contacting the substrate comprises a strength support layer A, a stress deformation layer and a stress absorption layer sequentially arranged in a direction away from the substrate; and / or The remaining multiple internal layers include a strength support layer A, a stress deformation layer and a stress absorption layer arranged in sequence in a direction away from the substrate, or include a strength support layer A, a stress absorption layer and a stress deformation layer arranged in sequence in a direction away from the substrate.

3. The component according to claim 1, wherein the metal in the metal nitride, the metal carbide or the metal carbonitride in the strength support layer A and the strength support layer B is independently selected from at least one of Cr, Al, Ti, Ta, Zr, Fe, Cu, Ni or V; The memory alloy in the stress-strain layer includes at least one of NiTi, NiTiCu, CuZn, CuZnAl, CuAlNi, NiMnGa, NiMnIn or CoNi; and / or The stress absorbing layer includes at least one of TiN and CrN.

4. The member according to claim 1, wherein each of the inner layers or the outer layer satisfies at least one of the following (1)-(11): (1) The hardness of the strength support layer A and the strength support layer B are independently HV2000 to HV3600; (2) The hardness of the stress deformation layer is HV300 to HV900; (3) The hardness of the stress absorbing layer is HV1500 to HV2000; (4) The hardness of the surface color layer is HV1500 to HV2600; (5) The size of the columnar crystals in the stress absorption layer is at least 100-300 nanometers; (6) The thickness of the strength support layer A and the strength support layer B are independently 0.3-1.5 μm; (7) The thickness of the stress deformation layer is 0.5-1.5 microns; (8) The thickness of the stress absorption layer is 0.2-1 micrometer; (9) The thickness of the surface color layer is 0.3-1 micron; (10) The total thickness of the coating is 8-20 μm; or (11) The total hardness of the coating is HV1500-HV3000.

5. A method for preparing a component according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) forming a strength support layer A on the surface of the substrate of the component; (2) forming a stress deformation layer on the strength support layer A; (3) forming a stress absorbing layer on the stress deformation layer; (4) repeating steps (1) to (3) for 4 to 15 cycles, wherein in each cycle, the order of the steps is independently steps (1), (2) and (3) or steps (1), (3) and (2); (5) forming a strength support layer B on the stress deformation layer or stress absorption layer obtained after the cycle of step (4); and (6) A surface color layer is formed on the strength support layer B.

6. The method according to claim 5, wherein the steps (1) and (5) adopt a multi-arc ion plating process, which includes introducing N gas, maintaining the gas pressure at 1-6 Pa, setting the target current at 60-200 A, the bias voltage at 60-200 V, turning on the target material of metal nitride, metal carbide or metal carbonitride, and the coating time is 10-20 min; The step (2) adopts a high-energy pulse magnetron sputtering process, which includes introducing Ar gas, maintaining the gas pressure at 0.1-0.8 Pa, the bias voltage at 0-60 V, setting the process parameters: power 8-10 kW, frequency 200-800 khz, pulse width 100-500 us, turning on the memory alloy target, and the coating time is 1-2 hours; The step (3) adopts a DC magnetron sputtering process, which includes introducing Ar and N gas, maintaining the gas pressure at about 0.5 Pa, turning on the Cr target, setting the target current to 20A, setting the bias voltage to 30V, and the coating time to 5-15min; and / or The step (6) adopts a high-energy pulse magnetron sputtering process, which includes introducing Ar and at least one of the following gases: N, C2H2 and O2, turning on the color target, and setting the process parameters: power 8-10KW, frequency 200-800khz, pulse width 100-500us, time 30-120min. The method according to claim 5 , wherein the material of the substrate comprises a steel substrate or an aluminum substrate.

8. The method according to claim 5, wherein the method further comprises a plasma cleaning process before step (1), and preferably the plasma cleaning process comprises: After the vacuum degree in the furnace reaches 5*10-3Pa and the temperature reaches 300 degrees, introduce Ar gas, maintain the gas pressure at 0.3Pa-0.9Pa, turn on the ion source, set the ion source voltage at 400-800V, the ion source duty cycle at 20-80%, set the bias voltage at 100-200V, and perform plasma cleaning for 5-60min.

9. A housing structure, characterized in that: The shell structure comprises a component according to any one of claims 1 to 4 or a component prepared by the method according to any one of claims 5 to 8.

10. An electronic device, characterized in that: The invention comprises an electronic device and a housing structure as claimed in claim 9, wherein the housing structure is located outside the electronic device.

Citation Information

Cited By

  • Conductive member containing coating and preparation method thereof

    CN121344545A